ANALISIS HUBUNGAN PEMBERIAN ASI EKSKLUSIF TERHADAP BERAT BADAN BAYI USIA 3–6 BULAN DI PUSKESMAS PAYUNG SEKAKI - Dewi Sartika Siagian; Lidya Siagian (LPPM Universitas Abdurrab, 2026)
Background: Infant growth and development are significantly influenced by adequate breastfeeding. According to the WHO (2023), global breastfeeding coverage has reached only 48%, still below the World Health Assembly’s target of 50%. Low exclusive breastfeeding rates can negatively impact infant growth, including weight gain. Objective: To determine the relationship between exclusive breastfeeding and weight gain in infants aged 3–6 months in the Payung Sekaki Health Center service area. Methods: This study used a quantitative design with a retrospective approach. The population in this study consisted of infants aged 3–6 months who were registered at the Payung Sekaki Community Health Center. The sample in this study consisted of 85 infants, and the sampling technique used was Cluster sampling. Data were obtained through primary data via questionnaires and secondary data via KMS (Health Card). Data analysis used the Chi-square test. Results: There was a significant relationship between exclusive breastfeeding and weight gain in infants aged 3–6 months (p < 0.05). Conclusion: Exclusive breastfeeding is associated with weight gain in infants aged 3–6 months. Mothers who have babies are expected to provide exclusive breastfeeding to their babies and continue until the baby is 2 years old.